2021
DOI: 10.1111/gtc.12830
|View full text |Cite
|
Sign up to set email alerts
|

The role of eutherian‐specific RTL1 in the nervous system and its implications for the Kagami‐Ogata and Temple syndromes

Abstract: RTL1 (also termed paternal expressed 11 (PEG11)) is considered the major imprinted gene responsible for the placental and fetal/neonatal muscle defects that occur in the Kagami–Ogata and Temple syndromes (KOS14 and TS14, respectively). However, it remains elusive whether RTL1 is also involved in their neurological symptoms, such as behavioral and developmental delay/intellectual disability, feeding difficulties, motor delay, and delayed speech. Here, we demonstrate that the mouse RTL1 protein is widely express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…PEG10 and RTL1 are expressed in many other tissues and organs besides the placenta ( Abed et al, 2019 ; Kitazawa et al, 2021 ). Recently, we demonstrated that mouse Rtl1 plays other important roles during the course of development, such as in fetal/neonatal skeletal muscle maturation as well as in functional activity of the central nervous system ( Kitazawa et al, 2020 , 2021 ). Therefore, it is possible that PEG10 has a multiplicity of functions across a range of organs and tissues.…”
Section: Resultsmentioning
confidence: 99%
“…PEG10 and RTL1 are expressed in many other tissues and organs besides the placenta ( Abed et al, 2019 ; Kitazawa et al, 2021 ). Recently, we demonstrated that mouse Rtl1 plays other important roles during the course of development, such as in fetal/neonatal skeletal muscle maturation as well as in functional activity of the central nervous system ( Kitazawa et al, 2020 , 2021 ). Therefore, it is possible that PEG10 has a multiplicity of functions across a range of organs and tissues.…”
Section: Resultsmentioning
confidence: 99%
“…A series of KO mouse studies of mammalian-specific RVD genes, including Peg10 , Rtl1/Peg11 , and Ldoc1/Sirh7/Rtl7 , as well as other Rtl/Sirh genes, has demonstrated that they exert important functions in the placenta and/or brain in mice and presumably humans [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Thus, the concept of mammalian-specific genes acquired from retroviruses is evidently well-supported, providing a useful model for approaching a variety of mammalian-specific features related to viviparous reproduction and the highly developed central nervous system in terms of genomic function.…”
Section: Discussionmentioning
confidence: 99%
“…RTL1/PEG11 plays essential roles in the placenta, muscle and brain and is the major gene responsible for the Kagami-Ogata and Temple syndromes, two genomic imprinting diseases. It is located on human chromosome 14 ( Kagami et al, 2008 ; Sekita et al, 2008 , Kitazawa et al, 2017 , 2020 , 2021 ). Both overexpression and deficiency lead to abnormalities in the placenta as well as a variety of neuromuscular and/or psychiatric symptoms ( Kitazawa et al, 2020 , 2021 ).…”
Section: Novel Functions Provided By Newly Acquired Imprinted Genes I...mentioning
confidence: 99%